Islamisasi Ilmu dan Integrasi Sains dalam Perspektif Pendidikan Islam - Endi Suhendi; Yanti Lestari; Jejen Ramdani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This article examines the concept of Islamization of knowledge and science integration within the framework of Islamic epistemology as an effort to overcome the dichotomy of knowledge that remains deeply rooted in the Islamic education system in Indonesia. Using a qualitative approach with library research method, this article analyzes the concept of Islamization of knowledge according to Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi, as well as the concept of science integration in contemporary Islamic perspective. The findings reveal that: (1) Islamization of knowledge constitutes an epistemological reconstruction that places tawhid as the foundation of all knowledge; (2) the integration of science and religion is complementary in nature; and (3) implementation in education still faces challenges including a dichotomous paradigm, limited teacher competence, and a curriculum not yet optimally integrated. This article offers constructive recommendations for the development of holistic and integrative Islamic education in the modern era.